Pathogenic Staphylococcus aureus Isolates from Postoperative Wounds of Hospitalized Patients - Smritikana Biswas; Kumari Dipti Rani; Prithwiraj Mukherjee; Chandradipa Ghosh (Al Ameen Medical College, 2010)
Staphylococcus sp., gram positive pyogenic bacteria located on skin, nose etc, secretes toxin that causes toxic shock syndrome, abscess, food poisoning and other infectious diseases. This study was carried out to identify and characterize the type of Staphylococcus sp. bacteria especially Staphylococcus aureus in the pus from postoperative wounds of hospitalized patients. From pus samples collected from twenty-four patients from Kharagpur Hospital, Paschim Medinipur, West Bengal, twenty-eight bacterial isolates were obtained. Among them twenty-five (89.2%) were appeared with golden yellow colonies which is usually formed by Staphylococcus aureus. Twenty-three (82.14%) of the bacterial isolates were Gram positive. Among them twenty isolates (86.9%) were further confirmed to be Staphylococcus aureus by their ability to produce Catalase enzyme (positive in Catalase test) and Coagulase enzyme (positive in Coagulase Test). Eighteen (90.00%) of these Staphylococcus aureus were found to liquefy gelatin (Gelatin hydrolysis test), were able to hydrolyze urea (Urea hydrolysis test) and were also l positive in Mannitol Fermentation Test. But there was no growth found of these isolates on MacConkey Agar, while sixteen isolates (80.00%) of Staphylococcus aureus were resistant to penicillin (50µg/ml). Moreover eighteen (90.00%) Staphylococcus aureus isolates were able to elaborate Hemolysin (Hemolysis test on Blood Agar media). Hence the bacterial isolates obtained from pus of postoperative wounds were predominantly pathogenic Staphylococcus aureus. So it can be concluded that careful treatment and postoperative measures to be taken to avoid serious health problem that may often be life threatening.